Creating an environment for thriving: An ethnographic exploration of a British decentralised Olympic and Paralympic sport organisation - Passaportis, M. J.; Brown, D. J.; Wagstaff, C. R.; Arnold, R.; Hays, K. (Psychology of Sport and Exercise, 2022)
Objectives The aims of this study were to explore the features of the athletic environment that influence thriving within a British Olympic and Paralympic sport organisation and to understand the interconnectedness of these factors across a range of individuals and contexts. These aims were pursued within a decentralised organisation that was undergoing a leader-led cultural change strategy.